The storyline as an exponent of the literary text's national-cultural specificity (on the material of the Andean countries' literature) - N M Firsova; Y A Karaseva (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2011)
The article is devoted to the study of the national-cultural potential of the literary text's storyline on the material of the literature of the Andean countries' historical and cultural zones. The basic extralinguistic factors that determine the theme and the storyline of the region's literary works are examined.